Increasing critical temperature on BPSCCO superconductors with addition of Al2O3. Issue 1 (May 2021) - Nasution, S F; Humaidi, S; Imaduddin, A; Darsono, N; Nugraha, H
Abstract: We have investigated the effect of addition of Al2 O3 in the manufacture of the BPSCCO superconductors using solid state reaction method. Precursors with consist of Bi2 O3, PbO2, SrCO3, CaCO3, and CuO powders were ground using mortar agate for 3 h. The samples were heated at 300°C for 6 h to remove the moisture in the powders, and then ground again for 6 h. Then the samples were calculated at 820°C for 20 h and then Al2 O3 (1wt% and 2wt%) were added and ground again. The powders were compacted with a diameter of 10 mm and a thickness of 2 mm and then sintered at 850°C for 30 h. The characterizations were carried out by using Cryogenic Magnet to determine the superconductivity properties, SEM-EDX to analyze the morphology and XRD to determine the phase formed. The resistivity versus temperature results showed the increase of Tc with the addition of Al2 O3 . Sample with 1wt% Al2 O3 has Tconset of 90 K and Tczero of 66 K, when the sample with 2wt% Al2 O3 has Tconset of 94 K and Tczero of 73 K. The morphology formed looks less homogeneous, the crystalline granules are melt-shaped, clumpy and there are porosity.